2019
DOI: 10.3847/2041-8213/ab451a
|View full text |Cite
|
Sign up to set email alerts
|

A NICER View of PSR J0030+0451: Implications for the Dense Matter Equation of State

Abstract: Both the mass and radius of the millisecond pulsar PSR J0030+0451 have been inferred via pulseprofile modeling of X-ray data obtained by NASA's NICER mission. In this Letter we study the implications of the mass-radius inference reported for this source by Riley et al. (2019) for the dense matter equation of state (EOS), in the context of prior information from nuclear physics at low densities. Using a Bayesian framework we infer central densities and EOS properties for two choices of highdensity extensions: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
219
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(236 citation statements)
references
References 78 publications
(90 reference statements)
16
219
0
1
Order By: Relevance
“…Next, we analyze the impact of systematic uncertainties arising from different priors for the EOS. We show that the priors used for the spectral EOS inference from GWs (Abbott et al 2018) allow for much stiffer EOSs than the priors in Raaijmakers et al (2019) and explain the reasons for these differences. Nevertheless, we find that the resulting EOS constraints are broadly consistent.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Next, we analyze the impact of systematic uncertainties arising from different priors for the EOS. We show that the priors used for the spectral EOS inference from GWs (Abbott et al 2018) allow for much stiffer EOSs than the priors in Raaijmakers et al (2019) and explain the reasons for these differences. Nevertheless, we find that the resulting EOS constraints are broadly consistent.…”
Section: Introductionmentioning
confidence: 88%
“…The spin for the two components in GW170817 is also assumed to be zero as we only use the posterior distribution on masses and tidal deformabilities in the case of the low-spin prior. In the left panel we show the comparison between the full prior distribution (black shaded region, 95% credible region bounded by the dark green contour) for the PP model with a 1.97 M cutoff (light green contour, as used in Raaijmakers et al 2019) and when updated by parameter estimation using the 2.14 M pulsar likelihood function (black dashed contour) from Cromartie et al (2019). Using a cutoff in the prior allows for slightly smaller radii than using the likelihood function: this is due to both the higher mass of the center of the pulsar likelihood function and the fact that the likelihood function gives more weight to an EOS with a maximum mass of 2.14 M than, e.g., 2.05 M .…”
Section: Bayesian Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this first two cases for neutron stars, we found that the stars with adiabatic index in the range 1.81 < Γ < 2.02 for EoS p = K ρ Γ and 2.05 < Γ < 2.40 for p = K ρ Γ 0 are optimal to reproduce the constrained maximum masses and the corresponding radius recently reported by Rezzolla et al (2018); Most et al (2018). We have carried out the same systematic search of parameters to cover the range of individual masses estimated from the GW170817 gravitational wave emission, the outcomes are showed in Figure 1 and values of K reported in Raaijmakers et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this work is to examine the maximum muon mass fractions and density profiles in NSs in the high-density EOS parameter space allowed by the available nuclear laboratory experiments and the latest observations of NS properties (mass, radius, and tidal deformability) including the simultaneous measurement of both the mass and radius of PSR J0030+0451 by the Neutron Star Interior Composition Explorer (NICER) Collaboration (Riley et al 2019;Raaijmakers et al 2019;Bilous et al 2019;Miller et al 2019;Bogdanov et al 2019a,b;Guillot et al 2019). The results of this work can be used as constrained model inputs in future studies of the new physics associated with the interactions between muonphilic DM and muons in NSs.…”
Section: Introductionmentioning
confidence: 99%